A Procedure for Changing a Behavioral Health Treatment During a Trial, with Case Example in Suicide Prevention. Issue 2 (2nd April 2020) - Britton, Peter C.; Conner, Kenneth R.; Maisto, Stephen A.
Abstract : During a trial, standardization can lock in a treatment that researchers learn is flawed and may be ineffective. In such cases, researchers typically decide between two options, continue the trial and monitor for iatrogenic effects or stop the trial. When faced with this dilemma while testing an adaptation of motivational interviewing to address suicidal ideation, our research team considered a third option, to correct the flaws in the intervention and study the effect on outcome. We explored the rationale for and against changing an intervention mid-trial and progressed through a series of steps to determine whether we should change the intervention, ultimately deciding to make changes and examine their impact. We developed a procedure that researchers can use to determine whether they should change an intervention during a trial, how to implement the changes, and how to redesign their study. When faced with evidence that a treatment is ineffective, researchers should consider changing the intervention and examining the effects of the changes on outcome. Such decisions may be particularly relevant in trials examining life-threatening outcomes. Making and studying these changes may increase the potential for the study to identify a treatment that produces a desired outcome.